2016
DOI: 10.1590/0037-8682-0128-2015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites and risk factors forspecific and multiple helminth infections in a remote city of the Brazilian Amazon

Abstract: Introduction: Few studies have described the risk factors of intestinal parasitic infections in the Amazon. Methods: A crosssectional survey was performed in a City of the State of Amazonas (Brazil) to estimate the prevalence of intestinal parasites and determine the risk factors for helminth infections. Results: Ascaris lumbricoides was the most prevalent parasite. The main risk factors determined were: not having a latrine for A. lumbricoides infection; being male and having earth or wood fl oors for hookwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
4
14
0
1
Order By: Relevance
“…We also identified statistically significant differences in infection rates between men and women. Several investigations have reported a higher prevalence of parasitic infection in males than females [ 48 , 49 ]. A possible explanation is the higher engagement of males in farming activities.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified statistically significant differences in infection rates between men and women. Several investigations have reported a higher prevalence of parasitic infection in males than females [ 48 , 49 ]. A possible explanation is the higher engagement of males in farming activities.…”
Section: Discussionmentioning
confidence: 99%
“…A . lumbricoides presented a more significant role in aboriginal communities of the region [ 68 , 69 ] suggesting that specific aspects of their socio-environmental condition favor the completion of its life cycle, maintenance and dispersion. Regarding the environmental samples, >70% of the surveyed sites were contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of school children in Belém , the State capital of Pará , the most frequently found helminths were Trichuris trichiura (57.6%), Ascaris lumbricoides (36.4%), and hookworms (24.3%) 10 . In contrast, a higher prevalence (65.3%) of helminth infections, mainly from A. lumbricoides, hookworms, and T. trichiura, has been reported in rural communities and in small urbanized settlements with limited sanitation in the Brazilian Amazon 11 . The prevalence of polyparasitism is also high in neglected populations; a prevalence of 12.2% was reported in Ethiopia 12 and is higher (56%) in Brazilian indigenous populations 13 .…”
Section: Introductionmentioning
confidence: 95%